Spectrophotometric Study of Nitrogen Base Adducts of Nickel(II)-4-methyl-8–quinolinate - T. Suresh; S. Santosh Kumar; N. M . Kottureshawara; M. Revanasidappa; Syed Khasim; Suresh (E-Journal of Chemistry)
Adduct formation constants have been determined by spectrophotometric study of a few typical bases with nickel(II) chelate of 4-methyl-8-quinolinol in chloroform. Bathochromic and hypsochromic shifts were observed in the visible range due to the adduct formation. Monobasic bases like pyridine, methyl substituted anilines and such other bases exhibit 1: 2 stoichiometry giving hexa – coordinated adductds . The dibasic bases such as 1,10-phenanthroline and 2,9- neocuproine exhibit 1 : 1 stoichiometry giving hexacoordinated adducts . The experimental results are discussed in terms of the basicity and steric effects of the various bases.